WORKSHOP MEMBUAT WEBSITE DENGAN VISUAL STUDIO CODE UNTUK SISWA SMP PGRI 363 - Adittiya Rino Nindra Pratama; Daffa Abdul Fattah Derian; Fitri Az Zahra; Kabhisatria Ardhy Haqqy; Kayla Fahira Dinia; Muhammad Naseer Kadarisman Wirapraja; Raka Indra Dwipangga; Rizka Aulia Putri; Wahyu Reza Habibi; Yulia Utari Rinjani; Iis Aisyah (Abdi Jurnal Publikasi, 2024)
This article presents the results of a community service program conducted at SMP PGRI 363 PondokPetir, focusing on equipping students with basic website creation skills using Visual Studio Code (VSC) and HTML. The workshop aimed to enhance students' technological literacy and inspire interest in pursuing advanced technological skills. The methods included direct practice and interactive discussions to ensure a comprehensive understanding. Feedback from participants indicated high satisfaction and improved competence in using VSC and HTML. The study highlights the importance of such workshops in bridging technological gaps in under-resourced schools.